1992
DOI: 10.1016/0014-5793(92)80437-l
|View full text |Cite
|
Sign up to set email alerts
|

Site‐directed mutants of human myeloperoxidase A topological approach to the heme‐binding site

Abstract: Two sitc.dircctcd mutants of human promycloperoxidase, MPO(HisJ%Ala) and MPO(His"%Ala), have been expressed in Chinese I-,;trster ovary cells and purified. Overall purification yields and apparent molecular masses of the mutant proteins were similur to those oT the wild-type enzyme. Both mutant spccics wcrc analyzed spectroscopicttlly to check the prcscncc of the hcmic iron in the proteinsand were assayed for peroxidasic aclivity, The data show that substitution of Hi?': leads to the loss, or to an inappropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…In line with this fact, iron depletion attenuates UPEC pathogenesis in a mouse and rat model of urinary tract infection and PN [44,45]. We found elevated expression of several AMPs with iron sequestering or heme-binding properties, namely calprotectin, NGAL, lactotransferrin, myeloperoxidase and eosinophil peroxidase [46][47][48][49]. Calprotectin is known to be produced and released by neutrophils, monocytes, and macrophages [23] and was found to be upregulated in acute renal allograft failure, AKI [23], obstructive nephropathy (ON) [24], ischemia/reperfusion (I/R) injury [50], staphylococcus infection-associated glomerulonephritis (SAGN) [25], and anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) [26].…”
Section: Discussionsupporting
confidence: 69%
“…In line with this fact, iron depletion attenuates UPEC pathogenesis in a mouse and rat model of urinary tract infection and PN [44,45]. We found elevated expression of several AMPs with iron sequestering or heme-binding properties, namely calprotectin, NGAL, lactotransferrin, myeloperoxidase and eosinophil peroxidase [46][47][48][49]. Calprotectin is known to be produced and released by neutrophils, monocytes, and macrophages [23] and was found to be upregulated in acute renal allograft failure, AKI [23], obstructive nephropathy (ON) [24], ischemia/reperfusion (I/R) injury [50], staphylococcus infection-associated glomerulonephritis (SAGN) [25], and anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) [26].…”
Section: Discussionsupporting
confidence: 69%
“…The failure to engineer MPO‐like properties into LPO by a single mutation was disappointing inasmuch as the reverse strategy used previously [15, 17], i.e. substituting Met‐409 in MPO by Gln, led to the loss of the chlorinating activity, to a red shift of the Soret peak from 428 nm to 413 nm and to the relative decrease in peroxidase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies using site‐directed mutagenesis of MPO revealed the nature of the bonds linking the heme group to the amino acid backbone and showed the importance of Met‐409 for enzymatic activity [15–17](Fig. 1 ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Site-directed mutagenesis studies [35], which are on the way, will show whether this suggestion is correct.…”
Section: Discussionmentioning
confidence: 96%